Supported catalyst, preparation method and application thereof, and method for regenerating organic amine solution
By loading Zr and M metals on the γ-Al2O3 support, the problems of high desorption temperature and high regeneration energy consumption during the CO2 capture process are solved, and efficient CO2 desorption at lower temperatures is achieved, reducing energy consumption and operating costs.
Patent Information
- Application Number
- CN202411705219.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-26
AI Technical Summary
In the prior art, monoethanolamine (MEA) as an organic amine solution has a high temperature required for desorption during CO2 capture, resulting in extremely high regeneration energy consumption, accounting for 70-80% of the total cost, and is prone to problems such as solution degradation and equipment corrosion.
A supported catalyst is used, which consists of Zr and M metals (Fe, Ni, Cu or Ce) supported on the γ-Al2O3 support. By regulating the Bronsted and Lewis acid sites of the catalyst, the CO2 desorption temperature is reduced and the regeneration energy consumption is reduced.
The CO2 desorption is achieved at a lower temperature (88-100°C), which significantly reduces the energy consumption of the organic amine solution, reduces the operating cost of the CO2 trapping method, and improves the cycling performance and stability of the catalyst.
Smart Images

Figure CN119500133A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon dioxide capture, and specifically relates to a supported catalyst and a preparation method and application thereof, and a method for regenerating an organic amine solution. Background Art
[0002] According to the "Climate Report 2023" released by the IPCC, the average concentration of atmospheric CO2 has climbed from 280ppm to 413ppm from 2011 to 2020 compared with 1850 to 1900, and the surface temperature has risen by 1.1℃, the highest in nearly 100,000 years. Excessive CO2 emissions are the main cause of global warming. Carbon capture, utilization and storage technology (CCUS) is an important path to achieve low-carbon development, including pre-combustion capture, oxygen-enriched combustion capture and post-combustion capture. Post-combustion capture technology includes membrane separation, solid adsorption and chemical absorption. At present, the organic amine solution absorption method represented by monoethanolamine (MEA) is the most widely used.
[0003] MEA has the advantages of low price, fast reaction kinetics, and high CO2 absorption capacity, but the temperature required for desorbing CO2 is as high as 110-130°C, resulting in extremely high regeneration energy consumption. The regeneration cost accounts for about 70-80% of the operating cost of the CO2 capture device, and it is easy to cause problems such as solution degradation and equipment corrosion. Summary of the invention
[0004] In view of this, the present invention provides a supported catalyst, a preparation method and application thereof, and a method for regenerating an organic amine solution. The supported catalyst provided by the present invention is used to catalyze the desorption of carbon dioxide by an organic amine solution, which can reduce the desorption temperature and significantly reduce the energy consumption for regenerating the organic amine solution.
[0005] In order to solve the above technical problems, the present invention provides a supported catalyst, comprising γ-Al2O3 and Zr and M metal supported on the surface and in the pores of the γ-Al2O3, wherein the M metal comprises Fe, Ni, Cu or Ce.
[0006] Preferably, the mass percentage of Zr in the supported catalyst is 9 to 11%;
[0007] The mass percentage of M metal in the supported catalyst is 9-11%.
[0008] Preferably, the specific surface area of the supported catalyst is 90.2 to 120.4 m 2 / g, mesopore surface area is 82.6~116.6m 2 / g, the average pore size is 7.64~8.82nm, and the acid site is 0.1905~0.2914mmol / g.
[0009] The present invention also provides a method for preparing the supported catalyst described in the above technical solution, comprising the following steps:
[0010] A soluble salt of Zr, a soluble salt of M metal, γ-Al2O3 and water are mixed and impregnated to obtain a primary supported catalyst;
[0011] The primary supported catalyst is calcined to obtain the supported catalyst.
[0012] Preferably, the mixing comprises the following steps:
[0013] dissolving the soluble salt of Zr in part of water to obtain a first active component solution;
[0014] dissolving the soluble salt of the M metal in the first active component solution to obtain a dual-active component solution;
[0015] Add γ-Al2O3 to the dual active component solution.
[0016] Preferably, the immersion time is 10 to 14 hours, and the immersion is accompanied by stirring;
[0017] After the impregnation, the method further comprises: evaporating the impregnated system, and drying the solid obtained after the evaporation to obtain the primary supported catalyst.
[0018] Preferably, the calcination temperature is 500-600° C., and the calcination holding time is 3-5 hours.
[0019] Preferably, the heating rate to the desired calcination temperature is 4-6°C / min.
[0020] The present invention also provides the use of the supported catalyst described in the above technical solution or the supported catalyst prepared by the preparation method described in the above technical solution in desorption of carbon dioxide from an organic amine solution.
[0021] The present invention also provides a method for regenerating an organic amine solution, comprising the following steps:
[0022] Adding a catalyst to an organic solution adsorbing carbon dioxide to desorb the carbon dioxide and collect the carbon dioxide;
[0023] The catalyst is the supported catalyst described in the above technical solution or the supported catalyst prepared by the preparation method described in the above technical solution;
[0024] The desorption temperature is 88-100°C.
[0025] The present invention provides a supported catalyst, including γ-Al2O3 and Zr and M metal supported on the surface and in the pores of the γ-Al2O3, wherein the M metal includes Fe, Ni, Cu or Ce. The supported catalyst provided by the present invention uses γ-Al2O3 with a large specific surface area, a mesoporous structure and excellent thermal stability as a carrier, which gives the supported catalyst a mesoporous structure and provides more effective contact between the catalytic active sites and reactants; the present invention uses Zr and M metal as active components to form a bimetallic supported solid acid catalyst; the synergistic effect of the bimetallic gives the supported catalyst stronger acidity and a higher content of Bronsted and Lewis acid sites, which promotes the two key steps of the desorption reaction, namely, the carbamate MEACOO — Cleavage and protonation of amine MEAH + Deprotonation. The supported catalyst provided by the present invention is used to catalyze the desorption of CO2-rich organic amine solution, which can desorb the solution at a relatively low temperature (88-100° C.) and reduce the regeneration cost of the organic amine CO2 capture method. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The XRD spectra of the supported catalysts prepared in Comparative Example 1 and Examples 1 to 4;
[0027] Figure 2 It is the adsorption-desorption isotherm curve diagram of the catalysts prepared in Comparative Example 1 and Examples 1 to 4;
[0028] Figure 3 NH3-TPD curves of the supported catalysts prepared in Comparative Example 1 and Examples 1 to 4;
[0029] Figure 4 The Py-IR spectra of the supported catalysts prepared in Examples 1 to 4;
[0030] Figure 5 is the temperature variation curve of desorption reaction;
[0031] Figure 6 It is a schematic diagram of the structure of the CO2 absorption-desorption reaction device used in the test example;
[0032] Figure 7 It is a graph showing the change of carbon dioxide desorption rate under the catalytic action of different catalysts;
[0033] Figure 8 The curve of carbon dioxide desorption under the catalytic action of different catalysts;
[0034] Fig. 9 The bar graph of carbon dioxide desorption in 1000s under the catalytic action of different catalysts and the dot-line graph of relative energy consumption;
[0035] Fig.10 This is a bar chart comparing the energy consumption of desorption for 1000s in each cycle of Test Example 2;
[0036] Fig.11 XRD spectra of ZrNi / γ-Al2O3 before and after 8 cycles;
[0037] Fig.12 This is a curve of CO2 load change in MEA solution with and without the effect of ZrNi / γ-Al2O3. DETAILED DESCRIPTION
[0038] The invention provides a supported catalyst, comprising gamma-Al2O3 and Zr and M metal supported on the surface and in the pores of the gamma-Al2O3, wherein the M metal comprises Fe, Ni, Cu or Ce.
[0039] As a specific embodiment of the present invention, the mass percentage of Zr in the supported catalyst can be 9-11%, or 10%; the mass percentage of M metal in the supported catalyst can be 9-11%, or 10%.
[0040] As a specific embodiment of the present invention, the specific surface area of the supported catalyst can be 90.2 to 120.4 m 2 / g, the mesoporous surface area can be 82.6~116.6m 2 / g, the average pore size can be 7.64-8.82nm, and the acid site can be 0.1905-0.2914mmol / g.
[0041] In the present invention, γ-Al2O3, as a Lewis acid, can promote the amine regeneration reaction of CO2-rich organic solution. It can not only provide an excellent channel structure for the reaction, but also play its own catalytic role. The present invention loads Zr and M metal elements such as Fe, Ni, Cu, Ce, etc. on γ-Al2O3 to form a bimetallic supported solid acid catalyst. By regulating the Bronsted and Lewis acid sites of the catalyst, the catalyst is given a mesoporous structure and a high specific surface area to increase the catalytic contact area of the reaction, and the CO2-rich MEA saturated solution is regenerated at a low temperature below 100°C, thereby effectively reducing the activation energy of the reaction, reducing the carbon dioxide desorption temperature, and reducing the regeneration energy consumption.
[0042] The supported catalyst provided by the invention has low cost, high circulation performance and is easy to recycle.
[0043] The present invention also provides a method for preparing the supported catalyst described in the above technical solution, comprising the following steps:
[0044] A soluble salt of Zr, a soluble salt of M metal, γ-Al2O3 and water are mixed and impregnated to obtain a primary supported catalyst;
[0045] The primary supported catalyst is calcined to obtain the supported catalyst.
[0046] In the present invention, a soluble salt of Zr, a soluble salt of M metal, γ-Al2O3 and water are mixed and then impregnated to obtain a primary supported catalyst. As a specific embodiment of the present invention, the mixing may include the following steps:
[0047] dissolving the soluble salt of Zr in water to obtain a first active component solution;
[0048] dissolving the soluble salt of the M metal in the first active component solution to obtain a dual active component solution;
[0049] Add γ-Al2O3 to the dual active component solution.
[0050] As a specific embodiment of the present invention, the soluble salt of Zr can be Zr(NO3)4·5H2O; the water can be deionized water. In the present invention, dissolving the soluble salt of Zr in water can be carried out under stirring conditions. The present invention has no special requirements for the stirring, as long as it can be completely dissolved. The present invention has no special requirements for the amount of water, as long as it can be completely dissolved.
[0051] As a specific embodiment of the present invention, the soluble salt of the M metal may be a soluble salt of Fe, a soluble salt of Ni, a soluble salt of Cu or a soluble salt of Ce; the soluble salt of Fe may be Fe(NO3)3·9H2O, the soluble salt of Ni may be NiCl2·6H2O, the soluble salt of Cu may be Cu(NO3)2·3H2O, and the soluble salt of Ce may be Ce(NO3)3·6H2O. As a specific embodiment of the present invention, the mass ratio of the M element in the soluble salt of the M metal to the Zr element in the soluble salt of Zr may be 0.8-1.2:1, or may be 1:1.
[0052] As a specific embodiment of the present invention, dissolving the soluble salt of the M metal in the first active component solution can be carried out under stirring conditions, and the stirring temperature can be 45-55°C, and can also be 50°C; the present invention has no special requirements on the stirring speed and time, as long as it can be mixed evenly.
[0053] As a specific implementation of the present invention, the mass ratio of the Zr element in the soluble salt of γ-Al2O3 and Zr can be 10:0.8-1.2, or can be 10:1.
[0054] As a specific embodiment of the present invention, the impregnation time can be 10 to 14 hours, or 11 to 12 hours; the impregnation can be accompanied by stirring; the present invention has no special limitation on the stirring, and stirring can enable the active components to fully enter the γ-Al2O3 channels.
[0055] As a specific embodiment of the present invention, the impregnation may further include: evaporating the impregnated system, and drying the solid obtained after the evaporation to obtain the primary supported catalyst. In the present invention, the evaporation temperature may be 80-90°C, or 85°C; the evaporation may be carried out in a water bath with constant temperature stirring. The present invention has no special requirements for the evaporation time, as long as the solvent can be removed. In the present invention, the drying temperature may be 100-120°C, or 110-115°C; the drying time may be 10-14h, or 11-12h; the drying may be carried out in an oven.
[0056] After obtaining the primary supported catalyst, the present invention calcines the primary supported catalyst to obtain the supported catalyst. As a specific embodiment of the present invention, the calcination may also include: crushing the primary supported catalyst. The present invention has no special requirements for the particle size of the product after the crushing. The present invention crushes or calcines the primary supported catalyst to facilitate sufficient calcination. As a specific embodiment of the present invention, the calcination temperature can be 500-600°C, or 550-580°C; the calcination insulation time can be 3-5h, or 4h; the heating rate to the temperature required for the calcination can be 4-6°C / min, or 5°C / min; the calcination can be carried out in a muffle furnace.
[0057] As a specific embodiment of the present invention, the calcination may further include: cooling the calcined product to room temperature; the room temperature may be 20-35°C, or 25-30°C.
[0058] The present invention also provides the use of the supported catalyst described in the above technical solution or the supported catalyst prepared by the preparation method described in the above technical solution in desorption of carbon dioxide from an organic amine solution.
[0059] The present invention also provides a method for regenerating an organic amine solution, comprising the following steps:
[0060] Adding a catalyst to an organic solution adsorbing carbon dioxide to desorb the carbon dioxide and collect the carbon dioxide;
[0061] The catalyst is the supported catalyst described in the above technical solution or the supported catalyst prepared by the preparation method described in the above technical solution;
[0062] The desorption temperature is 88-100°C, can be 91-98°C, and can also be 91-95°C.
[0063] As a specific embodiment of the present invention, the organic solution adsorbed with carbon dioxide can be a monoethanolamine solution adsorbed with carbon dioxide, or a monoethanolamine solution saturated with carbon dioxide.
[0064] As a specific embodiment of the present invention, the amount of catalyst added to the organic solution adsorbed with carbon dioxide can be 1-3 wt %, that is, 0.5-1.5 g of catalyst is added to 50 mL of the organic solution adsorbed with carbon dioxide.
[0065] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0066] Example 1
[0067] Dissolve Zr(NO3)4·5H2O (Aladdin) with a net Zr content of 0.6 g in 80 mL of deionized water and stir to dissolve to obtain a zirconium nitrate solution;
[0068] Add Fe(NO3)3·9H2O (Aladdin) with a net Fe content of 0.6 g to the zirconium nitrate solution and stir and mix evenly at 50°C to obtain a zirconium and iron dual active component solution;
[0069] Add 6 g of carrier γ-Al2O3 (Aladdin) to the dual active component solution of zirconium and iron, stir and immerse for 12 hours at room temperature (30°C), then stir and evaporate in a water bath at 85°C, place the solid obtained after evaporation in an oven, and dry it in an air atmosphere at 110°C for 12 hours to obtain a primary supported catalyst;
[0070] The primary supported catalyst solid material was crushed and placed in a muffle furnace. The temperature was increased from 25°C to 550°C at a heating rate of 5°C / min. The catalyst was calcined at 550°C for 4 hours and cooled to room temperature (30°C) to obtain a supported catalyst, recorded as ZrFe / γ-Al2O3.
[0071] Example 2
[0072] A supported catalyst was prepared according to the method of Example 1, except that Fe(NO3)3·9H2O (Aladdin) with a net Fe content of 0.6 g was replaced by NiCl2·6H2O (Aladdin) with a net Ni content of 0.6 g. The prepared supported catalyst was recorded as ZrNi / γ-Al2O3.
[0073] Example 3
[0074] A supported catalyst was prepared according to the method of Example 1, except that Fe(NO3)3·9H2O (Aladdin) with a net Fe content of 0.6 g was replaced by Cu(NO3)2·3H2O (Aladdin) with a net Cu content of 0.6 g. The prepared supported catalyst was recorded as ZrCu / γ-Al2O3.
[0075] Example 4
[0076] A supported catalyst was prepared according to the method of Example 1, except that Fe(NO3)3·9H2O (Aladdin) with a net Fe content of 0.6 g was replaced by Ce(NO3)3·6H2O (Aladdin) with a net Ce content of 0.6 g. The prepared supported catalyst was recorded as ZrCe / γ-Al2O3.
[0077] Comparative Example 1
[0078] Take γ-Al2O3 in Example 1 as a comparative example.
[0079] The supported catalysts prepared in Examples 1 to 4 were subjected to X-ray diffraction detection to obtain XRD spectra, such as Figure 1 As shown. Figure 1 It can be seen that the diffraction peaks of γ-Al2O3 in the supported catalyst are consistent with those reported in previous literature. The main characteristic peaks of ZrNi / γ-Al2O3 at 2θ of 66.89°, 45.88°, and 37.71° are well consistent with the (440), (400), and (311) crystal planes of Al2O3 (PDF#04-007-2615), indicating that the embedding of Zr and Ni does not significantly change the structure of the support γ-Al2O3. ZrCu / γ-Al2O3, ZrFe / γ-Al2O3, and ZrCe / γ-Al2O3 also have diffraction peaks at the (440) and (400) crystal plane positions corresponding to the support, but the peak intensity is reduced or shifted, and the characteristic peak at the (311) crystal plane position disappears or is weak. The XRD test results show that the supported catalysts prepared in the examples all maintain a structure that is basically consistent with the support, confirming the successful synthesis of the bimetallic supported γ-Al2O3 solid acid catalyst.
[0080] The supported catalysts prepared in γ-Al2O3 in Comparative Example 1 and Examples 1 to 4 were subjected to nitrogen adsorption and desorption test experiments to obtain adsorption and desorption isotherms, as shown in FIG. Figure 2 The structure and physical properties of the catalyst were calculated based on the adsorption-desorption isotherms, and the results are listed in Table 1.
[0081] Table 1 Physical properties of the catalysts prepared in Comparative Example 1 and Examples 1 to 4
[0082]
[0083]
[0084] According to the catalyst classification stipulated by the International Union of Pure and Applied Chemistry (IUPAC), the isotherm shapes and hysteresis loops of all catalysts belong to type IV and type H3, indicating that the supported catalyst provided by the present invention has mesoporous and slit-like pore structures.
[0085] Table 1 summarizes the textural properties of the five catalysts. The results show that the surface area, pore size and pore volume of the supported catalyst prepared in the embodiment are all lower than those of γ-Al2O3. The metal incorporated in the present invention fills part of the pores of the carrier and causes pore blockage. The pore volume difference between ZrM / γ-Al2O3 is small, and the mesoporous surface area is ranked as follows: ZrCe / γ-Al2O3>ZrFe / γ-Al2O3>ZrCu / γ-Al2O3>ZrNi / γ-Al2O3, and the pore size of ZrNi / γ-Al2O3 is the largest, which is 8.32nm. According to the IUPAC classification of the mesoporous diameter range, that is, 2≤d≤50nm, ZrM / γ-Al2O3 still belongs to mesoporous materials even after the average pore size is reduced. Higher mesoporous surface area and larger pore size are conducive to the exposure of the catalytic active sites of ZrM / γ-Al2O3 to the CO2-MEA solution, enhancing the effective contact and interaction between the catalyst and the reactants, thereby promoting the regeneration reaction of the organic amine solution.
[0086] The γ-Al2O3 in Comparative Example 1 and the supported catalysts prepared in Examples 1 to 4 were subjected to NH3-TPD measurement, and the desorption curves thereof are as follows: Figure 3As shown. According to the acid strength classification method, the NH3-TPD peak can be divided into three regions: weak acid region (below 200°C), medium-strong acid region (200-400°C) and strong acid region (above 400°C). According to the temperature range corresponding to the peak, all five catalysts contain weak acid and medium-strong acid sites, and ZrFe / γ-Al2O3 has the highest weak acid content. It is worth noting that only ZrNi / γ-Al2O3 has an obvious NH3 desorption peak in the high temperature zone, indicating that strong acid sites are generated after Zr and Ni are loaded on γ-Al2O3, and the acidity is stronger than other catalysts, which corresponds to the excellent catalytic desorption performance of ZrNi / γ-Al2O3.
[0087] The supported catalysts prepared in Examples 1 to 4 were subjected to pyridine adsorption infrared spectroscopy (Py-IR) to obtain a Py-IR spectrum. Figure 4 As shown, where L represents Lewis acid site and B represents Bronsted acid site. Figure 4 The acid content of the catalyst was calculated and the results are listed in Table 2.
[0088] Table 2 Acid sites of supported catalysts prepared in Examples 1 to 4
[0089]
[0090]
[0091] Depend on Figure 4 It can be seen that pyridine molecules attach to the surface of solid acid through different pathways, 1450 cm -1 and 1600cm -1 The sharp peak near 1540 cm corresponds to the LPy species formed by pyridine and L acid. -1 The absorption peak is related to B acid, 1490cm -1 The peak at is attributed to the simultaneous presence of L acid and B acid.
[0092] Table 2 summarizes the two acid contents and B / L ratio of ZrM / γ-Al2O3. The results show that the B acid and L acid contents of ZrNi / γ-Al2O3 are the highest, 0.0819mmol / g and 0.2095mmol / g, respectively. B acid can promote the dissociation of H2O molecules, produce a large number of active hydroxyl groups, provide the necessary protons for the desorption reaction, and play a key role in CO2 desorption; L acid comes from coordinated unsaturated metal atoms that can accept electron pairs, and can attack the isolated electron pairs of atoms, accelerating the CN bond breakage of the main reactant carbamate in the desorption process. It can be judged that the acid sites of ZrM / γ-Al2O3 play a key role in the CO2-MEA rich solution regeneration process.
[0093] The above performance test results show that the bimetallic supported solid acid catalyst ZrM / γ-Al2O3 provided by the present invention has excellent mesoporous structure and acidic properties, and has excellent catalytic performance in the desorption reaction of CO2-rich MEA solution.
[0094] Test Example 1
[0095] The catalytic desorption performance of the catalyst ZrM / γ-Al2O3 (M is Fe, Ni, Cu, Ce) prepared in Examples 1 to 4 was tested as follows:
[0096] The temperature change curve of the desorption reaction is obtained by controlling the temperature with the thermocouple in the water bath and recording the temperature data points in real time with the temperature sensor in the flask, such as Figure 5 shown.
[0097] A 100mL four-necked flask was used as the CO2 absorption-desorption reaction device of the MEA solution, equipped with a magnetic stirrer, a temperature sensor, a water bath, a desiccant, a condenser, a circulating condensation water tank and a power meter, etc., and an external non-dispersive infrared analyzer (NDIR) was used to measure the outlet CO2 concentration. A mixed gas of CO2 and N2 was introduced into a monoethanolamine (MEA) solution with a mass fraction of 30% (5mol / L), and after absorbing for a certain period of time at 40°C and 500rpm, a saturated solution with a loading of 0.5mol CO2 / molMEA was obtained. Add 2wt% (1g) of ZrM / γ-Al2O3 catalyst, heat to 91°C at 500rpm, keep constant temperature for 1h (3600s), use N2 at a flow rate of 100mL / min to purge the CO2 generated by the desorption reaction, and after condensation and drying, enter the gas analyzer to measure the CO2 concentration. Based on the measured data, calculate the CO2 desorption rate, desorption amount and relative energy consumption of desorption. The results are listed in Table 3. Figure 6 is a schematic diagram of the structure of the CO2 absorption-desorption reaction device; the carbon dioxide desorption rate variation curve under the catalytic action of different catalysts is shown in Figure 7 As shown in the figure, the variation curve of carbon dioxide desorption under the catalytic action of different catalysts is as follows Figure 8 As shown in the dot-line diagram, the relative energy consumption of carbon dioxide desorption under different catalysts is as follows: Fig. 9 shown.
[0098] The desorption performance calculation method is as follows:
[0099]
[0100]
[0101]
[0102]
[0103] In the formula, is the amount of CO2 desorption at time t, mmol; is the N2 flow rate, mL / min; x is the volume concentration of CO2 in the mixed gas, %; V m is the gas molar volume, L / mol; Dr is the CO2 desorption rate, mmol / min; E is the power consumption measured by the power meter, kJ; H i is the regeneration energy consumption of the added catalyst group, kJ / mol; H benchmark Refers to the energy consumption of MEA blank group, KJ / mol; RH is the relative energy consumption of the catalytic group compared with the blank group, %.
[0104] Table 3 Desorption performance of catalytic CO2-rich MEA solution
[0105]
[0106]
[0107] Table 3 shows that the four ZrM / γ-Al2O3 solid acids prepared in Examples 1 to 4 can improve the peak desorption rate by 37.4% to 46.86%, improve the maximum amplitude of the real-time desorption rate by 463.77% to 836.52%, increase the desorption amount by 64.79% to 81.66%, and reduce the relative energy consumption by 39.31% to 44.96%, compared with the blank group of MEA solution without adding catalyst. In Examples 1 to 4, ZrNi / γ-Al2O3 has the best catalytic desorption effect, which can improve the CO2 peak desorption rate by 46.86%, improve the maximum amplitude of the real-time CO2 desorption rate by 836.52%, increase the CO2 desorption amount by 81.66%, and reduce the relative energy consumption by 44.96%.
[0108] Combining Table 3 and Figure 7 It can be seen that with the extension of desorption time, the CO2 desorption rate of each group showed a trend of increasing first and then decreasing. The blank group reacted the slowest, followed by γ-Al2O3, and the ZrM / γ-Al2O3 group reacted significantly faster. Among them, ZrNi / γ-Al2O3 had the highest desorption kinetics, reaching the peak desorption rate of 1.92mmol / min at 548s, ZrCu / γ-Al2O3 reached 1.87mmol / min at 561s, γ-Al2O3 and the blank group reached 1.37mmol / min at 709s and 1.30mmol / min at 869s, respectively, indicating that ZrM / γ-Al2O3 can achieve a faster reaction rate at a lower temperature.
[0109] Figure 8It reflects the changing trend of CO2 desorption amount. In the early stage of the heating process, the desorption reaction progresses slowly. After 400 s, the growth rate of CO2 desorption amount in the catalytic group is significantly faster than that in the blank group, indicating that the catalyst reduces the energy barrier that needs to be overcome in the reaction. As the reaction enters the later stage, the relative increment of CO2 desorption amount between the catalytic group and the blank group gradually shrinks, and each group gradually approaches the chemical equilibrium of the desorption reaction.
[0110] Fig. 9 The results show that the relative heat loads of different catalysts are ranked as: ZrNi / γ-Al2O3 < ZrFe / γ-Al2O3 < ZrCe / γ-Al2O3 < ZrCu / γ-Al2O3 < γ-Al2O3 < blank group. ZrNi / γ-Al2O3 has the best energy consumption reduction effect, reducing the heat load by 44.96%, while γ-Al2O3 only reduces it by 17.7%. Therefore, after the bimetallic modification of γ-Al2O3, the reaction activation energy is effectively reduced, greatly promoting the detachment of CO2 from the solution and improving the bottleneck problem of high regeneration energy consumption of the CO2-MEA solution.
[0111] Test Example 2
[0112] The CO2 absorption-desorption cycle performance of ZrNi / γ-Al2O3 was tested 8 times according to the method of Test Example 1. The absorption process lasted for 1200 s, and the desorption process lasted for 3600 s. The specific test parameters were: 91 °C, 500 rpm, 50 mL of MEA solution with a CO2 loading of 0.5 mol / mol, and 2 wt% ZrNi / γ-Al2O3 was added.
[0113] Calculate the energy consumption for 1000 s of desorption and plot the results as a bar comparison chart, as Fig.10 shown. The CO2-MEA rich solution of ZrNi / γ-Al2O3 was tested for 8 absorption-desorption cycle reactions to prove the stability of its catalytic performance and structure. After 8 cycles, the energy consumption of the ZrNi / γ-Al2O3 catalytic group was still 23.1% lower than that of the blank group.
[0114] The ZrNi / γ-Al2O3 after 8 cycles was detected by XRD to obtain the XRD pattern, as Fig.11 shown. Fig.11 It can be seen that the XRD diffraction peaks of ZrNi / γ-Al2O3 before and after cycling are basically the same, and its structure has hardly changed, proving the stability of its structure and relatively high cycling performance.
[0115] Test Example 3
[0116] The CO2 absorption performance of ZrNi / γ-Al2O3 was tested according to the device of Test Example 1. The specific test parameters were: 50mL of 5mol / L MEA solution, 2wt% ZrNi / γ-Al2O3 was added, and CO2 was absorbed for 1200s at 40°C and 500rpm; the obtained curve of the change of CO2 absorption load of MEA solution with or without ZrNi / γ-Al2O3 was as shown in the figure. Fig.12 shown.
[0117] Depend on Fig.12 The results show that regardless of whether ZrNi / γ-Al2O3 is added or not, the CO2 loading capacity shows a trend of first rising rapidly and then slowly increasing, and finally entering a plateau period, and the two absorption curves are highly consistent. Therefore, within the experimental error range, ZrNi / γ-Al2O3 has no negative effect on the CO2 absorption performance of MEA solution.
[0118] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A supported catalyst, characterized in that It comprises γ-Al2O3 and Zr and M metal loaded on the surface and in the pores of the γ-Al2O3, wherein the M metal comprises Fe, Ni, Cu or Ce.
2. The supported catalyst according to claim 1, characterized in that The mass percentage of Zr in the supported catalyst is 9-11%; The mass percentage of M metal in the supported catalyst is 9-11%.
3. The supported catalyst according to claim 1, characterized in that The specific surface area of the supported catalyst is 90.2 to 120.4 m 2 / g, mesopore surface area is 82.6~116.6m 2 / g, the average pore size is 7.64~8.82nm, and the acid site is 0.1905~0.2914mmol / g.
4. The method for preparing the supported catalyst according to any one of claims 1 to 3, comprising the following steps: A soluble salt of Zr, a soluble salt of M metal, γ-Al2O3 and water are mixed and impregnated to obtain a primary supported catalyst; The primary supported catalyst is calcined to obtain the supported catalyst.
5. The preparation method according to claim 4, characterized in that: The mixing comprises the following steps: dissolving the soluble salt of Zr in part of water to obtain a first active component solution; dissolving the soluble salt of the M metal in the first active component solution to obtain a dual-active component solution; Add γ-Al2O3 to the dual active component solution.
6. The preparation method according to claim 4, characterized in that: The immersion time is 10 to 14 hours, and the immersion is accompanied by stirring; After the impregnation, the method further comprises: evaporating the impregnated system, and drying the solid obtained after the evaporation to obtain the primary supported catalyst.
7. The preparation method according to claim 4, characterized in that: The calcination temperature is 500-600° C., and the calcination holding time is 3-5 hours.
8. The preparation method according to claim 4 or 7, characterized in that: The heating rate to the desired calcination temperature is 4-6°C / min.
9. Use of the supported catalyst according to any one of claims 1 to 3 or the supported catalyst prepared by the preparation method according to any one of claims 4 to 8 in desorption of carbon dioxide from an organic amine solution.
10. A method for regenerating an organic amine solution, comprising the following steps: Adding a catalyst to an organic solution adsorbing carbon dioxide to desorb the carbon dioxide and collect the carbon dioxide; The catalyst is the supported catalyst according to any one of claims 1 to 3 or the supported catalyst prepared by the preparation method according to any one of claims 4 to 8; The desorption temperature is 88-100°C.
Citation Information
Patent Citations
Preparation method of supported catalyst for regenerating amine solution rich in carbon dioxide
CN106984333A
Method for preparing anthraquinone through anthracene oxidation method
CN108610250A
Preparation method of nano FeZr@composite molecular sieve catalyst for desorption of CO2-rich amine solution
CN110681413A
Preparation method and application of nickel modified molecular sieve catalyst for amine-rich regeneration
CN113663720A
Bimetal solid acid catalyst for reducing organic amine regeneration energy consumption and preparation method and application thereof
CN114260022A
Cited By
Composite catalytic material, preparation method and application thereof
CN122850178A